Characterization of COVID‐19 disease in pediatric oncology patients: The New York‐New Jersey regional experience. Issue 3 (18th December 2020) - Madhusoodhan, P. Pallavi; Pierro, Joanna; Musante, Jordan; Kothari, Prachi; Gampel, Bradley; Appel, Burton; Levy, Adam; Tal, Adit; Hogan, Laura; Sharma, Archana; Feinberg, Shari; Kahn, Alissa; et al.
Abstract: Purpose: Pediatric oncology patients undergoing active chemotherapy are suspected to be at a high risk for severe disease secondary to severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) infection; however, data to support this are lacking. We aim to describe the characteristics of coronavirus disease 2019 (COVID‐19) in this population and also its impact on pediatric cancer care in the New York region during the peak of the pandemic. Patients and Methods: This multicenter, retrospective study included 13 institutions. Clinical and laboratory information on 98 patients ≤21 years of age receiving active anticancer therapy, who tested positive for SARS‐CoV‐2 by nasopharyngeal swab polymerase chain reaction (PCR), was collected. Results: Of the 578 pediatric oncology patients tested for COVID‐19, 98 were positive, of whom 73 were symptomatic. Most experienced mild disease, 28 required inpatient management, 25 needed oxygen support, and seven required mechanical ventilation. There is a slightly higher risk of severe disease in males and obese patients, though not statistically significant. Persistent lymphopenia was noted in severe cases. Delays in cancer therapy occurred in 67% of SARS‐CoV‐2‐positive patients. Of four deaths, none were solely attributable to COVID‐19. The impact of the pandemic on pediatric oncology care was significant, with 54% of institutions reporting delays in chemotherapy, 46% delays in surgery, and 30% delays in transplant. Conclusion: In this large multi‐institutional cohort, we observed that mortality and morbidity from COVID‐19 amongst pediatric oncology patients were low overall, but higher than reported in general pediatrics. Certain subgroups might be at higher risk of severe disease. Delays in cancer care due to SARS‐CoV‐2 remain a concern.